Assessing Adequacy of University Rewards in Meeting Students’ Needs - Azhar, Adlan Afiq Musyrif bin; bin Mohd Suhaimi, Ahmad Hafizin; bin Abdul Nasir, Ahmad Hanif Haiqal; bin Mohd Razally, Ahmad Zikrullah (The Global Academia Publisher, 2024)
The project aims to assess the influence of university reward systems on students' development and determine whether current practices align with students' needs. By employing a comprehensive mixed-methods approach, data will be collected from a diverse range of university students through surveys and qualitative interactions. The study will evaluate the effectiveness and sufficiency of existing reward structures in addressing students' varied demands, including academic success, personal development, and wellbeing. It will examine different incentives, their perceived effectiveness, and their alignment with students' preferences and goals. The research will also identify gaps in reward structures, focusing on fairness, inclusion, and recognition of non-academic achievements. The study's results will inform universities in enhancing their incentive structures, fostering a supportive environment that meets students' needs. By promoting motivation, engagement, and overall well-being, the research aims to enhance academic achievement and facilitate holistic student development